The specifics of strength training for elite female wrestlers - Kuvanov, V.A.; Dmitriev, I.V.; Zakharov, A.E.; Ilyushchenko, S.A. (Theory and Practice of Physical Culture, 2026)
Objective of the study is to evaluate and analyse the effectiveness of using high-repetition and statodynamic modes of muscular activity among highly skilled female wrestlers during their physical preparation for sporting competitions. Methods and structure of the study. The experiment was conducted at the Comprehensive School of Higher Sports Excellence in St Petersburg, involving 22 highly skilled female wrestlers. Baseline measurements were taken before the start of the experiment, and again after 3 and 6 months. The main mechanism for utilising the statodynamic mode in the developed programme was the inclusion of additional sets performed with minimal weight and a reduced range of motion, without relaxation of the working muscle, and with a high number of repetitions. Results and conclusions. The results of the pedagogical experiment showed that a high-repetition training regime, used as a supplement to strength training as part of periodic adjustments to training loads, is an optimal and effective approach for reducing body fat and increasing muscle mass in female wrestlers during their training. A statistically significant improvement in results was observed after six months of the pedagogical experiment in most of the tests studied in the experimental group using a statodynamic training regime.